Computer vision and graphics : International Conference, ICCVG 2014, Warsaw, Poland, September 15-17, 2014. Proceedings - Kozera, Ryszard; Shin, Bok-Suk; Wojciechowski, Konrad; Chmielewski, Leszek J. (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the International Conference on Computer Vision and Graphics, ICCVG 2014, held in Warsaw, Poland, in September 2014. The 81 full papers presented were carefully reviewed and selected from various submissions. They cover various important aspects of computer vision and graphics.